Degradable thermosensitive hydrogel composite calcium-silicon-based bone cement and preparation method and application thereof
By using degradable temperature-sensitive hydrogels and modified calcium silicate systems in bone cement, combined with dopamine and growth factors, the problems of bone cement in mechanical properties, curing time and preparation process are solved, and effective support for bone tissue repair is achieved.
Patent Information
- Application Number
- CN202510207863.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-25
AI Technical Summary
The existing bone cement has problems with low mechanical properties and low matching degree with human bone tissue, long curing time, complex preparation process and difficult growth factor application problems, which affect the surgical effect and bone tissue repair process.
Degradable temperature-sensitive hydrogel composite calcium-silicon-based bone cement is used to enhance mechanical properties by modifying black phosphorus nanosheets in the calcium silicate system, dopamine accelerates the hydration reaction, and temperature-sensitive hydrogels provide degradation matching and biological activity, and growth factors promote cell proliferation and differentiation.
The mechanical properties of bone cement are achieved to match human bone tissue, shorten the curing time, simplify the preparation process, improve the matching of growth factor release, and promote bone tissue repair.
Smart Images

Figure CN119680017B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of biomedical materials, and in particular to a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement and a preparation method and application thereof. Background Art
[0002] In orthopedic surgery, bone cement plays a vital role and is widely used in scenarios such as filling bone defects and fixing implants, providing key support for bone repair and reconstruction. However, traditional bone cement has many shortcomings that are difficult to ignore. Taking polymethyl methacrylate bone cement as an example, although it has high mechanical strength and can provide effective support for bones in the short term, it cannot chemically bond with bone tissue due to its lack of biological activity. It simply fills the bone defects and is difficult to integrate into the normal physiological metabolism of bone tissue. At the same time, its non-degradability causes it to remain in the body for a long time. Over time, it may cause inflammatory reactions and irritate surrounding tissues. It may also cause problems such as decreased mechanical properties due to material aging, affecting the long-term effect of the surgery.
[0003] The emergence of calcium-silicon-based bone cement has brought new breakthroughs in the field of bone cement. It has certain biological activity and osteoconductivity, and can guide the growth of bone tissue to a certain extent and promote the repair of bone defects. However, calcium-silicon-based bone cement still has some shortcomings in practical applications. Its injectability is poor, and it is often difficult to distribute evenly when injected into the bone defect site, especially for bone defects with complex shapes, which are difficult to fill accurately, which may lead to insufficient filling of bone cement and affect the repair effect. In addition, its anti-collapse property needs to be improved. During the curing process, it is easily affected by the surrounding tissues and collapses, and it is impossible to form a stable structure to support the growth of bone tissue. In terms of degradation performance, the degradation rate of calcium-silicon-based bone cement is difficult to accurately control. It may degrade too quickly and fail to provide sufficient support for new bone growth, or degrade too slowly, hindering the normal growth of new bone.
[0004] In order to overcome these problems, attempts were made to combine thermosensitive hydrogel with calcium-silicon-based bone cement. Thermosensitive hydrogel has unique temperature response characteristics. In a low-temperature environment, it is in liquid state with good fluidity, which makes it easy to accurately inject into the bone defect through tools such as syringes. It can adapt well to the complex shape of bone defects and improve the injectability and filling accuracy of bone cement. When the temperature rises to body temperature, the thermosensitive hydrogel quickly undergoes a phase transition from liquid to solid, forming a stable three-dimensional network structure, which effectively enhances the anti-collapse property of bone cement.
[0005] However, the existing thermosensitive hydrogel composite calcium-silicon-based bone cement still has many problems in performance optimization: the mechanical properties are poorly matched with human bone tissue and cannot provide long-term stable mechanical support; the curing time is long, which increases surgical risks, costs, and patient pain and recovery time; the preparation process is complex, the cost is high, and it is not conducive to large-scale production and clinical application. It has high technical requirements for equipment and personnel, which increases production uncertainty and quality control difficulties. In addition, there are also many difficulties in introducing growth factors. Growth factors are difficult to disperse and load, and are prone to aggregation and inactivation. The release rate is also difficult to match the bone tissue repair process. Summary of the invention
[0006] The present application provides a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement and a preparation method and application thereof, so as to solve the problems in the prior art such as mismatched mechanical properties, long curing time, complex preparation process and difficulty in application of growth factors, which affect surgical effects and the progress of bone tissue repair.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The present invention provides a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement, and the bone cement is composed of the following weight ratios:
[0008] Modified calcium silicate system: 70-100 parts;
[0009] Thermosensitive hydrogel: 5-30 parts;
[0010] Growth factors: 1-5 parts.
[0011] Furthermore, the liquid-to-solid ratio of the bone cement is 0.3-1 ml / g, wherein the liquid phase is an aqueous dispersion of the thermosensitive hydrogel and the solid phase is a modified calcium silicate system.
[0012] Furthermore, the modified calcium silicate system is composed of the following weight ratios:
[0013] Dopamine: 0.5-2 parts;
[0014] Calcium carbonate: 5-15 parts;
[0015] Black phosphorus nanosheets: 0.1-1 part;
[0016] Sodium dihydrogen phosphate: 3-8 parts.
[0017] Furthermore, the calcium carbonate includes tricalcium silicate, dicalcium silicate and calcium sulfate hemihydrate, wherein the weight ratio is (4-6):(1-3):(2-4).
[0018] Furthermore, the black phosphorus nanosheet has a thickness of 1-5 layers and a sheet diameter of 50-200 nm.
[0019] Furthermore, the thermosensitive hydrogel is composed of the following weight ratios:
[0020] Polylactic acid: 10-20 parts;
[0021] Chitosan: 5-10 parts;
[0022] Nano hydroxyapatite: 1-5 parts.
[0023] Further, the preparation method of the thermosensitive hydrogel is as follows: dissolving chitosan in an acetic acid solution with a mass fraction of 2%-5%, stirring at 30-40°C for 2-4 hours to fully dissolve it, and adjusting the pH value to 5.5-6.5 with a sodium hydroxide solution; dissolving polylactic acid in dichloromethane to prepare a solution with a mass concentration of 10%-20%; adding nanohydroxyapatite to the chitosan solution, and using ultrasonic dispersion for 15-30 minutes to uniformly disperse it; under stirring conditions, slowly adding the polylactic acid solution to the chitosan solution containing nanohydroxyapatite at a rate of 1-2 drops per minute, stirring and reacting at 45-55°C for 4-5 hours to form a graft copolymer. After the reaction is completed, the product is placed in a dialysis bag, dialyzed in deionized water for 3-5 days to remove unreacted monomers and impurities, and finally freeze-dried for 24-48 hours to obtain a solid product of the thermosensitive hydrogel, which is prepared into an aqueous dispersion when used.
[0024] Furthermore, the growth factor is one or both of bone morphogenetic protein-2 and vascular endothelial growth factor.
[0025] The present invention also provides a method for preparing a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement, comprising:
[0026] Weigh the raw materials, mix tricalcium silicate, dicalcium silicate and calcium sulfate hemihydrate, and add dopamine, black phosphorus nanosheets and sodium dihydrogen phosphate at the same time, and ball mill for 12 hours at a ball mill speed of 300-500 rpm to obtain a modified calcium silicate system;
[0027] preparing a thermosensitive hydrogel and formulating it into an aqueous dispersion;
[0028] The prepared thermosensitive hydrogel aqueous dispersion is mixed with the modified calcium silicate system according to the liquid-to-solid ratio, stirred for 5-10 minutes at a stirring speed of 200-400 rpm, and then the growth factor is added, and the stirring is continued for 10-15 minutes to allow the growth factor and other components to be fully integrated, and finally a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement is prepared.
[0029] The present invention also provides an application of a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement in the preparation of a bone transplant substitute material.
[0030] The beneficial effects achieved by adopting the above-mentioned present invention are as follows:
[0031] 1. The present invention prepares a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement. The black phosphorus nanosheets in the modified calcium silicate system have excellent mechanical properties, and their unique two-dimensional structure can be evenly dispersed in the bone cement, playing a role in strengthening and toughening. Black phosphorus nanosheets and calcium carbonate form a stable skeleton structure through physical and chemical interactions, which effectively improves the overall mechanical properties of bone cement, making it more compatible with the mechanical properties of human bone tissue, and can provide long-term and stable mechanical support for bone tissue repair. For example, in the process of bone defect repair, the optimized mechanical properties ensure that the bone cement is not easily deformed and broken when subjected to daily stress, ensuring a stable environment for new bone growth;
[0032] 2. Secondly, dopamine is added for modification. Dopamine has good adhesion and reducibility. In the preparation process of the modified calcium silicate system, the phenolic hydroxyl group of dopamine can complex with the calcium ions on the surface of calcium silicate to form active sites, accelerate the formation of hydration products, thereby effectively shortening the curing time of bone cement and promoting the hydration reaction process of calcium silicate.
[0033] 3. The present invention prepares a thermosensitive hydrogel, wherein the thermosensitive hydrogel composed of polylactic acid and chitosan is degradable, and the degradation rate of the thermosensitive hydrogel matches the growth rate of new bone, which can provide sufficient support in the early stage of new bone growth, and can slowly degrade as new bone is gradually formed, making room for the growth of new bone, thereby avoiding the adverse effects on bone tissue repair caused by too fast or too slow degradation;
[0034] 4. In the prepared thermosensitive hydrogel, the ester group on the polylactic acid molecular chain and the hydroxyl group in the chitosan molecule undergo esterification reaction under certain temperature and stirring conditions to form an ester bond, thereby realizing the graft copolymerization of polylactic acid and chitosan. This graft copolymerization reaction combines the originally hydrophilic chitosan with the hydrophobic polylactic acid to form a polymer with certain thermosensitive properties; nanohydroxyapatite has a high specific surface area and surface activity, and can form physical adsorption and chemical bonding with chitosan and polylactic acid. It can fill the gaps in the polymer network, increase the cross-linking density of the hydrogel, thereby improving the hardness and compressive strength of the hydrogel, etc., making it closer to the mechanical properties of natural bone. On the other hand, the chemical composition of nanohydroxyapatite is similar to the inorganic components in human bones, and has good biological activity and osteoconductivity. It can promote cell adhesion, proliferation and differentiation, guide the growth of bone tissue, and make the thermosensitive hydrogel more suitable as a bone repair material.
[0035] 5. Thermosensitive hydrogel is liquid at low temperatures and has good fluidity. It can significantly improve the injectability of bone cement, allowing it to be smoothly injected into bone defects of various complex shapes to achieve precise filling. When the temperature rises to body temperature, the thermal motion of the polymer molecular chains intensifies, the interaction between the molecular chains is enhanced, and a phase transition occurs, changing from liquid to solid, forming a stable three-dimensional network structure, which is intertwined with the modified calcium silicate system, enhancing the anti-collapse property of bone cement. This thermosensitive property mainly stems from the changes in the glass transition temperature of polylactic acid and the hydrogen bonding between chitosan molecular chains with temperature. At low temperatures, polylactic acid is in a glassy state, the flexibility of the molecular chains is poor, the interaction with the chitosan molecular chains is weak, and the system is liquid; when the temperature rises to close to body temperature, the polylactic acid molecular chains gradually enter a highly elastic state, the flexibility of the molecular chains increases, and a tighter network structure is formed with the chitosan molecular chains through hydrogen bonds and other interactions, thereby causing the hydrogel to undergo a phase transition and form a solid state;
[0036] 6. The present invention adds production factors, and the growth factors work synergistically with the modified calcium silicate system and the thermosensitive hydrogel, greatly enhancing the biological activity of bone cement. Bone morphogenetic protein-2 can induce mesenchymal stem cells to differentiate into osteoblasts and promote the formation of bone tissue; vascular endothelial growth factor can promote angiogenesis and provide sufficient nutrition supply for the growth of bone tissue. The modified calcium silicate system itself has certain biological activity and osteoconductivity, and the unique three-dimensional network structure of the thermosensitive hydrogel provides a good load carrier for the growth factor. During the preparation process, the growth factor can be evenly dispersed in the network structure of the thermosensitive hydrogel, avoiding the problem of aggregation and inactivation. At the same time, the temperature response characteristics of the thermosensitive hydrogel enable the release rate of the growth factor to be regulated according to changes in the body's environmental temperature. When bone cement is injected into the body, as the temperature rises to body temperature, the thermosensitive hydrogel undergoes a phase transition from liquid to solid. This transition process can control the release rate of the growth factor, so that it matches the bone tissue repair process and continues to play a role in promoting bone tissue repair;
[0037] 7. The preparation method of the present invention is relatively simple. In the preparation process of the modified calcium silicate system, dopamine, black phosphorus nanosheets, sodium dihydrogen phosphate and the components of the calcium silicate system are mixed and ball-milled in a ball mill, and the modified calcium silicate system can be prepared in one step, which reduces the cumbersome multi-step reaction and separation and purification steps. The preparation process of the thermosensitive hydrogel is also relatively simple. The thermosensitive hydrogel with good performance can be obtained by solution mixing, ultrasonic dispersion and graft copolymerization. This simplified preparation process reduces the requirements for equipment and personnel technology, is conducive to large-scale production and clinical application, and also reduces production costs, improves production efficiency and product quality stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0039] Figure 1 A schematic diagram of a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement component provided by an embodiment of the present invention;
[0040] Figure 2 A flow chart of a method for preparing a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement provided in an embodiment of the present invention;
[0041] Figure 3 A schematic diagram of an X-ray of a patient provided by one embodiment of the present invention;
[0042] Figure 4 A schematic diagram of injection of a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement provided by one embodiment of the present invention;
[0043] Figure 5 A schematic diagram of an X-ray of a patient with a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement provided by one embodiment of the present invention;
[0044] Figure 6 A microstructure diagram of a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement provided in Example 1 of the present invention;
[0045] Figure 7 A microstructure diagram of a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement provided in Example 2 of the present invention;
[0046] Figure 8 A microstructure diagram of a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement provided in Example 3 of the present invention;
[0047] Fig. 9 A microstructure diagram of a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement provided in Example 4 of the present invention;
[0048] Fig.10 A microstructure diagram of a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement provided in Example 5 of the present invention;
[0049] Fig.11 A microstructure diagram of a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement provided in Comparative Example 1 of the present invention;
[0050] Fig.12 A microstructure diagram of a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement provided in Comparative Example 2 of the present invention;
[0051] Fig.13A microstructure diagram of a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement provided in Comparative Example 3 of the present invention;
[0052] Fig.14 A schematic diagram of the absorbance of a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement provided by multiple embodiments of the present invention;
[0053] Fig.15 A schematic diagram of alkaline phosphatase activity of a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement provided by multiple embodiments of the present invention;
[0054] Fig.16 A comparison chart of production factors of a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0055] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.
[0056] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.
[0057] The present invention will be further described below in conjunction with the following examples.
[0058] Example 1
[0059] The present invention provides a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement, such as Figure 1 As shown, bone cement is composed of the following weight proportions:
[0060] Modified calcium silicate system: 70 parts;
[0061] Thermosensitive hydrogel: 5 parts;
[0062] Growth Factors: 1 part.
[0063] The liquid-to-solid ratio of the bone cement is 0.3 ml / g, wherein the liquid phase is an aqueous dispersion of the thermosensitive hydrogel and the solid phase is a modified calcium silicate system.
[0064] Wherein, the modified calcium silicate system is composed of the following weight ratios:
[0065] Dopamine: 0.5 parts;
[0066] Calcium carbonate: 5 parts;
[0067] Black phosphorus nanosheets: 0.1 parts;
[0068] Sodium dihydrogen phosphate: 3 parts.
[0069] Among them, calcium carbonate includes tricalcium silicate, dicalcium silicate and calcium sulfate hemihydrate, wherein the weight ratio is 4:1:2.
[0070] Among them, the thickness of the black phosphorus nanosheet is 1-5 layers, and the diameter of the sheet is 50-200nm.
[0071] The thermosensitive hydrogel is composed of the following weight ratios:
[0072] Polylactic acid: 10 parts;
[0073] Chitosan: 5 parts;
[0074] Nano hydroxyapatite: 1 part.
[0075] Among them, the preparation method of the thermosensitive hydrogel is as follows: dissolve chitosan in an acetic acid solution with a mass fraction of 2%-5%, stir at 30-40°C for 2-4 hours to fully dissolve it, and adjust the pH value to 5.5-6.5 with a sodium hydroxide solution; dissolve polylactic acid in dichloromethane to prepare a solution with a mass concentration of 10%-20%; add nanohydroxyapatite to the chitosan solution, and use ultrasonic dispersion for 15-30 minutes to make it uniformly dispersed; under stirring conditions, slowly add the polylactic acid solution to the chitosan solution containing nanohydroxyapatite at a rate of 1-2 drops per minute, stir and react at 45-55°C for 4-5 hours to form a graft copolymer. After the reaction is completed, the product is placed in a dialysis bag, dialyzed in deionized water for 3-5 days to remove unreacted monomers and impurities, and finally freeze-dried for 24-48 hours to obtain a solid product of the thermosensitive hydrogel, which is prepared into an aqueous dispersion when used.
[0076] Among them, the growth factors are bone morphogenetic protein-2 and vascular endothelial growth factor.
[0077] The present invention also provides a method for preparing a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement, such as Figure 2 As shown, including:
[0078] Weigh the raw materials, mix tricalcium silicate, dicalcium silicate and calcium sulfate hemihydrate, and add dopamine, black phosphorus nanosheets and sodium dihydrogen phosphate at the same time, and ball mill for 12 hours at a ball mill speed of 300-500 rpm to obtain a modified calcium silicate system;
[0079] preparing a thermosensitive hydrogel and formulating it into an aqueous dispersion;
[0080] The prepared thermosensitive hydrogel aqueous dispersion is mixed with the modified calcium silicate system according to the liquid-to-solid ratio, stirred for 5-10 minutes at a stirring speed of 200-400 rpm, and then the growth factor is added, and the stirring is continued for 10-15 minutes to allow the growth factor and other components to be fully integrated, and finally a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement is prepared.
[0081] The present invention also provides an application of a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement in the preparation of a bone transplant substitute material.
[0082] Specifically, Figure 3 As shown in the figure, X-ray examinations of patients with lumbar disc herniation and lumbar instability showed varying degrees of changes in the physiological curvature of the lumbar spine, with significant narrowing of the intervertebral space and bone hyperplasia on the edges of some vertebrae. The stability of the affected vertebral segment decreased, and there were signs of mild dislocation or slippage between the vertebrae. The density of the intervertebral disc area was uneven, indicating a herniated disc, and the protruding part exerted a certain amount of pressure on the surrounding tissues. At the same time, there was no obvious damage to the bone structure of adjacent vertebrae, but the arrangement of the trabeculae was slightly disordered, which may be related to the stress changes caused by long-term lumbar instability. Figure 4 As shown in the figure, when patients with lumbar disc herniation and lumbar instability undergo lumbar intervertebral fusion surgery, bone cement is filled into the intervertebral fusion cage or between vertebrae. Its good injectability makes the filling process simpler and more efficient, and it can be evenly distributed in the fusion site. Figure 5 As shown in the figure, the solidified bone cement is tightly combined with the vertebral body, which enhances the stability between the fusion cage and the vertebral body and promotes bone fusion between the vertebrae. At the same time, the degradation characteristics of bone cement make it gradually absorbed after bone fusion is completed, avoiding the adverse reactions that may be caused by long-term retention in the body, and providing reliable protection for the patient's spinal function recovery.
[0083] Example 2
[0084] The present invention provides a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement, such as Figure 1 As shown, bone cement is composed of the following weight proportions:
[0085] Modified calcium silicate system: 78 parts;
[0086] Thermosensitive hydrogel: 10 parts;
[0087] Growth factors: 2 parts.
[0088] The liquid-to-solid ratio of the bone cement is 0.4 ml / g, wherein the liquid phase is an aqueous dispersion of the thermosensitive hydrogel and the solid phase is a modified calcium silicate system.
[0089] Wherein, the modified calcium silicate system is composed of the following weight ratios:
[0090] Dopamine: 1 part;
[0091] Calcium carbonate: 8 parts;
[0092] Black phosphorus nanosheets: 0.3 parts;
[0093] Sodium dihydrogen phosphate: 4 parts.
[0094] Among them, calcium carbonate includes tricalcium silicate, dicalcium silicate and calcium sulfate hemihydrate, wherein the weight ratio is 4:2:3.
[0095] Among them, the thickness of the black phosphorus nanosheet is 1-5 layers, and the diameter of the sheet is 50-200nm.
[0096] The thermosensitive hydrogel is composed of the following weight ratios:
[0097] Polylactic acid: 12 parts;
[0098] Chitosan: 6 parts;
[0099] Nano hydroxyapatite: 2 parts.
[0100] Among them, the preparation method of the thermosensitive hydrogel is as follows: dissolve chitosan in an acetic acid solution with a mass fraction of 2%-5%, stir at 30-40°C for 2-4 hours to fully dissolve it, and adjust the pH value to 5.5-6.5 with a sodium hydroxide solution; dissolve polylactic acid in dichloromethane to prepare a solution with a mass concentration of 10%-20%; add nanohydroxyapatite to the chitosan solution, and use ultrasonic dispersion for 15-30 minutes to make it uniformly dispersed; under stirring conditions, slowly add the polylactic acid solution to the chitosan solution containing nanohydroxyapatite at a rate of 1-2 drops per minute, stir and react at 45-55°C for 4-5 hours to form a graft copolymer. After the reaction is completed, the product is placed in a dialysis bag, dialyzed in deionized water for 3-5 days to remove unreacted monomers and impurities, and finally freeze-dried for 24-48 hours to obtain a solid product of the thermosensitive hydrogel, which is prepared into an aqueous dispersion when used.
[0101] Among them, the growth factors are bone morphogenetic protein-2 and vascular endothelial growth factor.
[0102] The present invention also provides a method for preparing a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement, such as Figure 2 As shown, including:
[0103] Weigh the raw materials, mix tricalcium silicate, dicalcium silicate and calcium sulfate hemihydrate, and add dopamine, black phosphorus nanosheets and sodium dihydrogen phosphate at the same time, and ball mill for 12 hours at a ball mill speed of 300-500 rpm to obtain a modified calcium silicate system;
[0104] preparing a thermosensitive hydrogel and formulating it into an aqueous dispersion;
[0105] The prepared thermosensitive hydrogel aqueous dispersion is mixed with the modified calcium silicate system according to the liquid-to-solid ratio, stirred for 5-10 minutes at a stirring speed of 200-400 rpm, and then the growth factor is added, and the stirring is continued for 10-15 minutes to allow the growth factor and other components to be fully integrated, and finally a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement is prepared.
[0106] Example 3
[0107] The present invention provides a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement, such as Figure 1 As shown, bone cement is composed of the following weight proportions:
[0108] Modified calcium silicate system: 85 parts;
[0109] Thermosensitive hydrogel: 15 parts;
[0110] Growth factors: 3 parts.
[0111] The liquid-to-solid ratio of the bone cement is 0.6 ml / g, wherein the liquid phase is an aqueous dispersion of the thermosensitive hydrogel and the solid phase is a modified calcium silicate system.
[0112] Wherein, the modified calcium silicate system is composed of the following weight ratios:
[0113] Dopamine: 1.2 parts;
[0114] Calcium carbonate: 10 parts;
[0115] Black phosphorus nanosheets: 0.5 parts;
[0116] Sodium dihydrogen phosphate: 5 parts.
[0117] Among them, calcium carbonate includes tricalcium silicate, dicalcium silicate and calcium sulfate hemihydrate, wherein the weight ratio is 5:2:3.
[0118] Among them, the thickness of the black phosphorus nanosheet is 1-5 layers, and the diameter of the sheet is 50-200nm.
[0119] The thermosensitive hydrogel is composed of the following weight ratios:
[0120] Polylactic acid: 15 parts;
[0121] Chitosan: 8 parts;
[0122] Nano hydroxyapatite: 3 parts.
[0123] Among them, the preparation method of the thermosensitive hydrogel is as follows: dissolve chitosan in an acetic acid solution with a mass fraction of 2%-5%, stir at 30-40°C for 2-4 hours to fully dissolve it, and adjust the pH value to 5.5-6.5 with a sodium hydroxide solution; dissolve polylactic acid in dichloromethane to prepare a solution with a mass concentration of 10%-20%; add nanohydroxyapatite to the chitosan solution, and use ultrasonic dispersion for 15-30 minutes to make it uniformly dispersed; under stirring conditions, slowly add the polylactic acid solution to the chitosan solution containing nanohydroxyapatite at a rate of 1-2 drops per minute, stir and react at 45-55°C for 4-5 hours to form a graft copolymer. After the reaction is completed, the product is placed in a dialysis bag, dialyzed in deionized water for 3-5 days to remove unreacted monomers and impurities, and finally freeze-dried for 24-48 hours to obtain a solid product of the thermosensitive hydrogel, which is prepared into an aqueous dispersion when used.
[0124] Among them, the growth factors are bone morphogenetic protein-2 and vascular endothelial growth factor.
[0125] The present invention also provides a method for preparing a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement, such as Figure 2 As shown, including:
[0126] Weigh the raw materials, mix tricalcium silicate, dicalcium silicate and calcium sulfate hemihydrate, and add dopamine, black phosphorus nanosheets and sodium dihydrogen phosphate at the same time, and ball mill for 12 hours at a ball mill speed of 300-500 rpm to obtain a modified calcium silicate system;
[0127] preparing a thermosensitive hydrogel and formulating it into an aqueous dispersion;
[0128] The prepared thermosensitive hydrogel aqueous dispersion is mixed with the modified calcium silicate system according to the liquid-to-solid ratio, stirred for 5-10 minutes at a stirring speed of 200-400 rpm, and then the growth factor is added, and the stirring is continued for 10-15 minutes to allow the growth factor and other components to be fully integrated, and finally a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement is prepared.
[0129] Example 4
[0130] The present invention provides a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement, such as Figure 1 As shown, bone cement is composed of the following weight proportions:
[0131] Modified calcium silicate system: 90 parts;
[0132] Thermosensitive hydrogel: 22 parts;
[0133] Growth factors: 4 parts.
[0134] The liquid-to-solid ratio of the bone cement is 0.8 ml / g, wherein the liquid phase is an aqueous dispersion of the thermosensitive hydrogel and the solid phase is a modified calcium silicate system.
[0135] Wherein, the modified calcium silicate system is composed of the following weight ratios:
[0136] Dopamine: 1.5 parts;
[0137] Calcium carbonate: 12 parts;
[0138] Black phosphorus nanosheets: 0.8 parts;
[0139] Sodium dihydrogen phosphate: 6 parts.
[0140] Among them, calcium carbonate includes tricalcium silicate, dicalcium silicate and calcium sulfate hemihydrate, wherein the weight ratio is 6:2:3.
[0141] Among them, the thickness of the black phosphorus nanosheet is 1-5 layers, and the diameter of the sheet is 50-200nm.
[0142] The thermosensitive hydrogel is composed of the following weight ratios:
[0143] Polylactic acid: 18 parts;
[0144] Chitosan: 9 parts;
[0145] Nano hydroxyapatite: 4 parts.
[0146] Among them, the preparation method of the thermosensitive hydrogel is as follows: dissolve chitosan in an acetic acid solution with a mass fraction of 2%-5%, stir at 30-40°C for 2-4 hours to fully dissolve it, and adjust the pH value to 5.5-6.5 with a sodium hydroxide solution; dissolve polylactic acid in dichloromethane to prepare a solution with a mass concentration of 10%-20%; add nanohydroxyapatite to the chitosan solution, and use ultrasonic dispersion for 15-30 minutes to make it uniformly dispersed; under stirring conditions, slowly add the polylactic acid solution to the chitosan solution containing nanohydroxyapatite at a rate of 1-2 drops per minute, stir and react at 45-55°C for 4-5 hours to form a graft copolymer. After the reaction is completed, the product is placed in a dialysis bag, dialyzed in deionized water for 3-5 days to remove unreacted monomers and impurities, and finally freeze-dried for 24-48 hours to obtain a solid product of the thermosensitive hydrogel, which is prepared into an aqueous dispersion when used.
[0147] Among them, the growth factors are bone morphogenetic protein-2 and vascular endothelial growth factor.
[0148] The present invention also provides a method for preparing a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement, such as Figure 2As shown, including:
[0149] Weigh the raw materials, mix tricalcium silicate, dicalcium silicate and calcium sulfate hemihydrate, and add dopamine, black phosphorus nanosheets and sodium dihydrogen phosphate at the same time, and ball mill for 12 hours at a ball mill speed of 300-500 rpm to obtain a modified calcium silicate system;
[0150] preparing a thermosensitive hydrogel and formulating it into an aqueous dispersion;
[0151] The prepared thermosensitive hydrogel aqueous dispersion is mixed with the modified calcium silicate system according to the liquid-to-solid ratio, stirred for 5-10 minutes at a stirring speed of 200-400 rpm, and then the growth factor is added, and the stirring is continued for 10-15 minutes to allow the growth factor and other components to be fully integrated, and finally a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement is prepared.
[0152] Example 5
[0153] The present invention provides a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement, such as Figure 1 As shown, bone cement is composed of the following weight proportions:
[0154] Modified calcium silicate system: 100 parts;
[0155] Thermosensitive hydrogel: 30 parts;
[0156] Growth factors: 5 parts.
[0157] The liquid-to-solid ratio of the bone cement is 1 ml / g, wherein the liquid phase is an aqueous dispersion of the thermosensitive hydrogel and the solid phase is a modified calcium silicate system.
[0158] Wherein, the modified calcium silicate system is composed of the following weight ratios:
[0159] Dopamine: 2 parts;
[0160] Calcium carbonate: 15 parts;
[0161] Black phosphorus nanosheets: 1 part;
[0162] Sodium dihydrogen phosphate: 8 parts.
[0163] Among them, calcium carbonate includes tricalcium silicate, dicalcium silicate and calcium sulfate hemihydrate, wherein the weight ratio is 6:3:4.
[0164] Among them, the thickness of the black phosphorus nanosheet is 1-5 layers, and the diameter of the sheet is 50-200nm.
[0165] The thermosensitive hydrogel is composed of the following weight ratios:
[0166] Polylactic acid: 20 parts;
[0167] Chitosan: 10 parts;
[0168] Nano hydroxyapatite: 5 parts.
[0169] Among them, the preparation method of the thermosensitive hydrogel is as follows: dissolve chitosan in an acetic acid solution with a mass fraction of 2%-5%, stir at 30-40°C for 2-4 hours to fully dissolve it, and adjust the pH value to 5.5-6.5 with a sodium hydroxide solution; dissolve polylactic acid in dichloromethane to prepare a solution with a mass concentration of 10%-20%; add nanohydroxyapatite to the chitosan solution, and use ultrasonic dispersion for 15-30 minutes to make it uniformly dispersed; under stirring conditions, slowly add the polylactic acid solution to the chitosan solution containing nanohydroxyapatite at a rate of 1-2 drops per minute, stir and react at 45-55°C for 4-5 hours to form a graft copolymer. After the reaction is completed, the product is placed in a dialysis bag, dialyzed in deionized water for 3-5 days to remove unreacted monomers and impurities, and finally freeze-dried for 24-48 hours to obtain a solid product of the thermosensitive hydrogel, which is prepared into an aqueous dispersion when used.
[0170] Among them, the growth factors are bone morphogenetic protein-2 and vascular endothelial growth factor.
[0171] The present invention also provides a method for preparing a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement, such as Figure 2 As shown, including:
[0172] Weigh the raw materials, mix tricalcium silicate, dicalcium silicate and calcium sulfate hemihydrate, and add dopamine, black phosphorus nanosheets and sodium dihydrogen phosphate at the same time, and ball mill for 12 hours at a ball mill speed of 300-500 rpm to obtain a modified calcium silicate system;
[0173] preparing a thermosensitive hydrogel and formulating it into an aqueous dispersion;
[0174] The prepared thermosensitive hydrogel aqueous dispersion is mixed with the modified calcium silicate system according to the liquid-to-solid ratio, stirred for 5-10 minutes at a stirring speed of 200-400 rpm, and then the growth factor is added, and the stirring is continued for 10-15 minutes to allow the growth factor and other components to be fully integrated, and finally a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement is prepared.
[0175] Comparative Example 1
[0176] A degradable thermosensitive hydrogel composite calcium-silicon-based bone cement, which differs from Example 1 only in that black phosphorus nanosheets and dopamine are not added to the modified calcium silicate system, and the reduced amount of black phosphorus nanosheets and dopamine is distributed to calcium carbonate, and the remaining preparation components are the same as those in Example 1.
[0177] Comparative Example 2
[0178] A degradable thermosensitive hydrogel composite calcium-silicon-based bone cement, which differs from Example 1 only in that nano-hydroxyapatite and polylactic acid are not added to the thermosensitive hydrogel, and the reduced amount of nano-hydroxyapatite and polylactic acid is distributed to chitosan, and the remaining preparation components are the same as those in Example 1.
[0179] Comparative Example 3
[0180] A degradable thermosensitive hydrogel composite calcium-silicon-based bone cement, which differs from Example 1 only in that black phosphorus nanosheets and dopamine are not added to the modified calcium silicate system, nano-hydroxyapatite is not added to the thermosensitive hydrogel, the reduced amounts of black phosphorus nanosheets and dopamine are allocated to calcium carbonate, and the reduced amounts of nano-hydroxyapatite and polylactic acid are allocated to chitosan, and the remaining preparation components are the same as those in Example 1.
[0181] Performance Testing
[0182] The degradable thermosensitive hydrogel composite calcium-silicon-based bone cement prepared in Examples 1-5 and Comparative Examples 1-3 were respectively made into standard cylindrical specimens, and axial pressure was applied to the specimens at a loading rate of 0.5 mm / min. The maximum load when the specimens were destroyed was recorded, and the compressive strength and bending strength were calculated; using a Vicat needle tester, the modulated bone cement was placed in a specific mold, and in a constant temperature and humidity environment of 37°C and 100% relative humidity, a Vicat needle was vertically inserted into the surface of the bone cement at regular intervals. When the Vicat needle insertion depth was 1-2 mm, the time at this time was recorded as the curing time. The results are shown in Table 1 below.
[0183] Table 1 Performance test
[0184]
[0185] As shown in Table 1, in Examples 1 to 5, with the change of the proportion of components such as the modified calcium silicate system, the thermosensitive hydrogel and the growth factor, the compressive strength and the flexural strength are on an upward trend as a whole, and the curing time is on a downward trend. This shows that there is a synergistic effect between the components, which jointly enhances the mechanical properties of bone cement. The black phosphorus nanosheets in the modified calcium silicate system have excellent mechanical properties, and their two-dimensional structure can be evenly dispersed in the bone cement to play an enhancing and toughening role. In addition, factors such as the complexation of dopamine with calcium ions on the surface of calcium silicate, the interaction between the thermosensitive hydrogel and the modified calcium silicate system jointly promote the curing reaction of bone cement, so that the curing time is shortened. Some of the data in Example 5 have decreased slightly, which may be due to the slight difference in the synergistic effect caused by the change in the proportion of certain components, but the overall data remain at a high level. While Comparative Example 1 lacks black phosphorus nanosheets and dopamine, Comparative Example 2 lacks nanohydroxyapatite and polylactic acid, and Comparative Example 3 lacks the above-mentioned key components at the same time, and its compressive strength and flexural strength are significantly lower than those of the embodiment, and the curing time is the longest. This indicates that components such as black phosphorus nanosheets, dopamine and nanohydroxyapatite not only affect the mechanical properties, but also play an important regulatory role in the curing process of bone cement. The lack of these components will lead to a slower curing reaction.
[0186] The degradable thermosensitive hydrogel composite calcium-silicon-based bone cement prepared in Examples 1-5 and Comparative Examples 1-3 were placed in simulated human body fluid and incubated in a constant temperature shaking incubator at 37° C. The specimens were taken out regularly, rinsed with deionized water, freeze-dried, and weighed, and the mass loss rate was calculated to evaluate the degree of degradation. The results are shown in Table 2 below.
[0187] Table 2 Degradation degree
[0188]
[0189] At the same time, the surface microstructure changes of the specimens were observed by scanning electron microscopy, such as Figure 6-13 As shown in Table 2, the morphological evolution of the material during the degradation process was obtained. Figure 6-13It can be seen that from 1 month to 3 months, the degradation rate of Examples 1-5 shows a stable upward trend, and bone cement can be degraded relatively stably and continuously in a simulated human body fluid environment. This characteristic of matching the degradation rate with the new bone growth rate is conducive to the gradual replacement of bone cement by new bone during bone tissue repair, providing space for new bone growth. As the degradation proceeds, it can be observed that the material surface gradually increases in pores and loose structures, which corresponds to the higher degradation rate, indicating that the material is constantly being eroded and dissolved; and the degradation rate of Comparative Examples 1-3 is significantly lower than that of the embodiment. Among them, although Comparative Example 1 only lacks black phosphorus nanosheets and dopamine, the degradation rate is also reduced to a certain extent. Comparative Example 2 lacks nanohydroxyapatite and polylactic acid. Polylactic acid, as an important component of thermosensitive hydrogel, is degradable in itself. In the thermosensitive hydrogel system, polylactic acid molecular chains are intertwined with other components, and its degradation process will affect the stability of the entire hydrogel network structure. When polylactic acid is missing, the three-dimensional network structure of the hydrogel becomes tighter and more stable, hindering the contact and reaction between the simulated body fluid and the internal components of the bone cement, thereby slowing down the degradation rate; Comparative Example 3 lacks multiple key components at the same time, and has the lowest degradation rate. Its microstructure may change relatively little, and the surface is relatively dense, which also reflects the inhibitory effect of component deficiency on the degradation behavior of bone cement in simulated body fluids.
[0190] The degradable thermosensitive hydrogel composite calcium-silicon-based bone cement prepared in Examples 1-5 and Comparative Examples 1-3 were used to inoculate bone marrow mesenchymal stem cells in 96-well plates containing different bone cement extracts. After culturing for 1, 3, 5, and 7 days, a cell proliferation test solution was added to each well and incubated for 4 hours. Then, dimethyl sulfoxide was added to dissolve the crystals, and the absorbance was measured at a wavelength of 490 nm using an enzyme marker. Fig.14 As shown, the cell proliferation was evaluated, as shown in Table 3. After 3, 7, and 14 days of cell culture, the cells were collected, lysed with a cell lysis buffer, and the alkaline phosphatase activity in the lysate was determined using an alkaline phosphatase detection kit. Fig.15 As shown, the degree of alkaline phosphatase activity is shown in the following Table 3.
[0191] Table 3 Alkaline phosphatase activity
[0192]
[0193] At the same time, the growth factor-loaded bone cement specimens were placed in simulated body fluids, and a certain amount of immersion fluid was taken out at different time points. The concentration of growth factors in the immersion fluid was detected using an enzyme-linked immunosorbent assay kit, such as Fig.16 shown.
[0194] From Table 3 and Fig.16As shown, from Example 1 to Example 5, the cell proliferation rate in 7 days steadily increased from 150% to 190%, showing the positive synergistic effect between the modified calcium silicate system, thermosensitive hydrogel and growth factor in the degradable thermosensitive hydrogel composite calcium-silicon-based bone cement. This synergistic effect provides a more suitable growth microenvironment for bone marrow mesenchymal stem cells and promotes frequent cell division. At the same time, at the 14-day detection time point, the alkaline phosphatase activity of Examples 1 to 5 gradually increased from 50U / L to 70U / L, indicating that the ability of the bone cement to induce bone marrow mesenchymal stem cells to differentiate into osteoblasts is continuously enhanced, accelerating the formation of bone tissue.
[0195] Compared with the experimental examples, the cell proliferation rate and alkaline phosphatase activity of Comparative Examples 1 to 3 are significantly lower than those of the embodiments. Due to the lack of black phosphorus nanosheets and dopamine, the cell proliferation rate of Comparative Example 1 is only 100%, and the alkaline phosphatase activity is 30U / L; Comparative Example 2 lacks nanohydroxyapatite and polylactic acid, the cell proliferation rate is 120%, and the alkaline phosphatase activity is 40U / L; Comparative Example 3 lacks multiple key components at the same time, and the cell proliferation rate is the lowest, only 80%, and the alkaline phosphatase activity is only 25U / L. These results show that the lack of key components destroys the microenvironment that was originally conducive to cell growth, affects the normal activation of cell proliferation signaling pathways and cell adhesion and living environment, thereby limiting the cell proliferation ability and differentiation process into osteoblasts. This may be because the lack of key components affects the release of growth factors, resulting in cells being unable to obtain sufficient stimulation signals to start or maintain normal proliferation and differentiation processes.
[0196] In summary, the degradable thermosensitive hydrogel composite calcium-silicon-based bone cement proposed in the present invention and its preparation method and application, through the modified calcium silicate system, wherein the black phosphorus nanosheets enhance the mechanical properties of the material with its unique two-dimensional structure, and the addition of dopamine accelerates the hydration reaction and shortens the curing time. In addition, the thermosensitive hydrogel is formed by graft copolymerization of polylactic acid and chitosan, and is embedded with nanohydroxyapatite to improve hardness and biological activity. Its thermosensitive properties ensure that the material is stably cured at body temperature and matches the growth rate of new bone. The synergistic effect of growth factors further promotes cell proliferation, differentiation and angiogenesis, providing strong biological activity support for bone tissue repair. The entire preparation process is simple and efficient, which not only reduces production costs, but also improves production efficiency and product quality stability. As a result, the problems of mechanical property mismatch, long curing time, complex preparation process and growth factor application problems in the prior art are solved, affecting the surgical effect and bone tissue repair process.
[0197] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A degradable thermosensitive hydrogel composite calcium-silicon-based bone cement, characterized in that: The bone cement is composed of the following weight proportions: Modified calcium silicate system: 70-100 parts; Thermosensitive hydrogel: 5-30 parts; Growth factors: 1-5 parts; Wherein, the modified calcium silicate system is composed of the following weight ratios: Dopamine: 0.5-2 parts; Calcium carbonate: 5-15 parts; Black phosphorus nanosheets: 0.1-1 part; Sodium dihydrogen phosphate: 3-8 parts; Wherein, the thermosensitive hydrogel is composed of the following weight ratios: Polylactic acid: 10-20 parts; Chitosan: 5-10 parts; Nano hydroxyapatite: 1-5 parts.
2. A degradable thermosensitive hydrogel composite calcium-silicon-based bone cement according to claim 1, characterized in that: The liquid-to-solid ratio of the bone cement is 0.3-1 ml / g, wherein the liquid phase is an aqueous dispersion of a thermosensitive hydrogel and the solid phase is a modified calcium silicate system.
3. The degradable thermosensitive hydrogel composite calcium-silicon-based bone cement according to claim 1, characterized in that: The calcium carbonate includes tricalcium silicate, dicalcium silicate and calcium sulfate hemihydrate, wherein the weight ratio is (4-6):(1-3):(2-4).
4. The degradable thermosensitive hydrogel composite calcium-silicon-based bone cement according to claim 1, characterized in that: The black phosphorus nanosheet has a thickness of 1-5 layers and a sheet diameter of 50-200 nm.
5. The degradable thermosensitive hydrogel composite calcium-silicon-based bone cement according to claim 1, characterized in that: The preparation method of the thermosensitive hydrogel is as follows: dissolving chitosan in an acetic acid solution with a mass fraction of 2%-5%, stirring at 30-40°C for 2-4 hours to fully dissolve it, and adjusting the pH value to 5.5-6.5 with a sodium hydroxide solution; dissolving polylactic acid in dichloromethane to prepare a solution with a mass concentration of 10%-20%; adding nano-hydroxyapatite to the chitosan solution, and uniformly dispersing it by ultrasonic dispersion for 15-30 minutes; under stirring conditions, slowly adding the polylactic acid solution to the chitosan solution containing nano-hydroxyapatite at a speed of 1-2 drops per minute, stirring and reacting at 45-55°C for 4-5 hours to form a graft copolymer; after the reaction is completed, placing the product in a dialysis bag, dialyzing it in deionized water for 3-5 days to remove unreacted monomers and impurities, and finally freeze-drying it for 24-48 hours to obtain a solid product of the thermosensitive hydrogel, which is prepared into an aqueous dispersion when used.
6. The degradable thermosensitive hydrogel composite calcium-silicon-based bone cement according to claim 1, characterized in that: The growth factor is one or both of bone morphogenetic protein-2 and vascular endothelial growth factor.
7. A method for preparing the degradable thermosensitive hydrogel composite calcium-silicon-based bone cement according to any one of claims 1 to 6, characterized in that: The preparation method comprises: Weigh the raw materials, mix tricalcium silicate, dicalcium silicate and calcium sulfate hemihydrate, and add dopamine, black phosphorus nanosheets and sodium dihydrogen phosphate at the same time, and ball mill for 12 hours at a ball mill speed of 300-500 rpm to obtain a modified calcium silicate system; preparing a thermosensitive hydrogel and formulating it into an aqueous dispersion; The prepared thermosensitive hydrogel aqueous dispersion is mixed with the modified calcium silicate system according to the liquid-to-solid ratio, stirred for 5-10 minutes at a stirring speed of 200-400 rpm, and then the growth factor is added, and the stirring is continued for 10-15 minutes to allow the growth factor and other components to be fully integrated, and finally a degradable thermosensitive hydrogel composite calcium-silicon-based bone cement is prepared.
8. Use of the degradable thermosensitive hydrogel composite calcium-silicon-based bone cement according to any one of claims 1 to 6 in the preparation of bone transplant substitute materials.
Citation Information
Patent Citations
Implantable fusion devices comprising bioactive glass
US20190099515A1
Injection-type magnesium-based carbon nanotube composite microsphere activated calcium phosphate biological bone adhesive and method for preparation thereof and application thereof
WO2022088634A1